Students' perceived parenting style and family type and their academic performance. - Marfil, Mae Antoinette G.
This study was conducted to show the relationship between students' preceived parenting style and their academic performance; and to know if a student's academic performance varies according to family type. The respondents were 74 4th year high school students of Guimbal National High School, Guimbal who were chosen using the stratified random sampling. The Parental Authority Questionnaire (Buri, 1991) was used to gather data. The tools for analysis were the Pearson correlation and chi square. Results showed that authoritative parenting style is positively correlated to students' academic performance. And that a student's academic performance varies according to family types, students from nuclear family type performs better compared to students from extended and solo parenting family types